Aesthetic and Religius Value of Rebana Music Art in Darul Ulum Islamic Boarding School Ngembalrejo Bae Kudus - Azmi, Ulya Zakaria; Utomo, Udi; Triyanto, Triyanto (Universitas Negeri Semarang, 2018)
As one of the culture element, art is human nature that is bestowed by Allah for an activity that involves creative ability in expressing beauty, truth and goodness. The aesthetic value of Al-Chulafa’s rebana art is not only as an entertainment for the students of Darul Ulum Islamic boarding school and the society, but also as a music accompaniment to the song in praise of Prophet Muhammad to remind and give good advice to the performers as well as the audiences and grow religious values. The goal of this study is to analyze the aesthetic value and religious value of Al-Chulafa’s rebana art. Data analysis technique is taken by reducing, presenting and verifying data. The research is qualitative descriptive approach using design of case study located in Ngembalrejo Village, Bae Kudus. Data source in this study are primary and secondary source and techniques of collecting data are doing observation, interview and document studies. Technique of data validity is triangulation of the source while data analysis technique is taken by reducing data, presenting data, and verifying data. The result shows that the aesthetic value of Al-Chulafa's rebana art shows unity and harmony, which has the principle of organic unity, principle of theme, principle of thematic variation, principle of balance, principle of evolution, and principle of hierarchy. While the religious values in the art of rebana gives a positive impact to the spirituality development of its personnel, which is covered in five dimensions of religious behavior they are the value of belief, the value of religious practice, the value of experience, the value of religious knowledge and the value of religious practice.